The Coping Behavior in Booth Tarkington’s The Magnificent Ambersons: An Individual Psychological Approach - Radityo Tri Nugroho (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2019)
The object of this paper is the novel Ambersons by Newton Booth Tarkington. This study focuses on the major question of how George Amberson Minafer, the major character, copes with his problem. The researcher employs a qualitative method in analyzing the novel. Following the data gathering and analysis, the writer draws two conclusions: first, George Amberson Minafer copes with his problem through changing his behavior, from negative behavior to positive one. He becomes more optimistic, independent and caring for his family. Second, George Amberson Minafer copes his problem through his action. He has the courage to admit his mistake. He asks forgiveness to the man that he hurt most.